Penerapan Nesting terhadap Perubahan Suhu Tubuh pada Bayi dengan Berat Badan Lahir Rendah di Ruang Perinatologi RSUD Batang - R. Teguh Ady P; Dwi Retnaningsih (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Low Birth Weight (LBW) infants are among the leading causes of neonatal morbidity and mortality in Indonesia. This condition results from the immaturity of organ systems, including thermoregulation, making infants vulnerable to hypothermia. One non-pharmacological intervention to maintain body temperature stability is the nesting technique, which positions the baby in a flexed posture similar to the intrauterine condition using soft rolled cloths as a “nest.” This case study aimed to determine the effect of nesting on body temperature changes in LBW infants in the perinatology room of RSUD Batang. The study used a descriptive case study with a nursing process approach involving five LBW infants (<2500 g, spontaneous breathing). The intervention involved applying nesting for 30 minutes daily over three consecutive days. Body temperature was measured before and after the intervention using a digital thermometer. The results showed an increase in body temperature in all subjects. The average temperature before intervention was 35.9°C and increased to 36.6°C after three days of nesting therapy. This indicates that nesting effectively helps maintain body temperature stability in LBW infants by providing comfort, reducing stress, and conserving body energy. In conclusion, nesting is an effective evidence-based nursing intervention for improving body temperature in LBW infants and is recommended for perinatology care settings.